2010
DOI: 10.1523/jneurosci.1264-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Core Mammalian Target of Rapamycin Signaling Pathway Is Critical for Cue-Induced Reinstatement of Cocaine Seeking in Rats

Abstract: Relapse to drug seeking was studied using a rodent model of reinstatement induced by exposure to drug-related cues. The mammalian target of rapamycin (mTOR), a serine/threonine protein kinase that regulates cell growth and survival by controlling translation in response to nutrients and growth factors, has been demonstrated to be involved in neuronal adaptations that underlie drug addiction and learning and memory. We investigated the potential role of the mTOR signaling pathway in relapse to cocaine seeking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 78 publications
(78 reference statements)
5
91
1
Order By: Relevance
“…In accordance with findings of Lu and colleagues (Wang et al, 2010b), we found that cocaine self-administration (FR5) was unaffected by intra-NAC rapamycin injections (Experiment 3). However, i.c.v.…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with findings of Lu and colleagues (Wang et al, 2010b), we found that cocaine self-administration (FR5) was unaffected by intra-NAC rapamycin injections (Experiment 3). However, i.c.v.…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responsupporting
confidence: 92%
“…Notably, rapamycin treatment did not affect locomotor activity or produce other non-specific effects on baseline motivational performance (ie, FR5 cocaine responding), findings that support recent demonstrations that rapamycin does not affect responding for a natural rewards (Neasta et al, 2010;Wang et al, 2010b). Thus, reductions in baseline mTORC1 in drug naive rats may be insufficient to alter general motivation status.…”
Section: Effect Of Mtorc1 Inhibition In Cocaine Naı¨ve Ratssupporting
confidence: 74%
See 1 more Smart Citation
“…The western blot method was based on our previous studies (Ren et al, 2013;Wang et al, 2010;Xue et al, 2012). All rats were decapitated without anesthesia 1 h after the end of extinction.…”
Section: Western Blot Assaysmentioning
confidence: 99%
“…6,22 Rapamycin (50 µg/0.5 µl) was also purchased from Sigma and dissolved in saline containing 5% DMSO, as described in a previous report. 23 We purchased D-serine (50 µg/0.5 µL) from Beijing Redwood Fine Chemical Co. Ltd. and dissolved it in saline containing 2% DMSO, as described in a previous report. 24 All drugs and vehicles were bilaterally infused into the mPFC at a volume of 0.5 µl per side.…”
Section: Drugsmentioning
confidence: 99%